BEYOND THE USING DIALECT AND JAVANESE SONG LYRICS: AN ANALYSIS OF AFFIXATION INTHE USING DIALECT AND ITS COMPARISON TO JAVANESE - Pramuditha, Mayang (2014)
The current study entitled "Beyond the Using dialect and Javanese Song Lyrics: An analysis of Affixation in the Using Dialect and Its Comparison to Javanese" investigates the processes of affixations which are realized in the Usingdialect and Javanese song lyrics. This study also identifies the differences in using the same affixes in the Using dialect and Javanese. The data were taken from 27 song lyrics in the Usingdialect and 27 song lyrics in Javanese, which were analyzed qualitatively. This study employs the theory of affixation from Kridalaksana (2007), Aryatipitipun (2007), Chaer (2007) and Ramlan (2009). The analysis reveals that the processes of affixation which are realized in the Using dialect are similar to Javanese. The data found that the affixation processes occur in both the Usingdialect and Javanese include six types of affixes (prefixes, simulfixes, infixes, suffixes, confixes and affixes combination). Those five of six types of affixation (prefixes, simulfixes, suffixes, confixes and affixes combination) are realized through morphophonemic process which include changes of phoneme, addition, deletion and assimilation. With regard to the differences, the study discovers that there are differences in using the different allomorph of simulfix {n-}. In the Using dialect, simulfix {n-} changes to allomorph {nge-} when it is attached to the bases which are begun with initial phoneme /l/ and /d/ (two syllables) through morphophonemic process. It is different from Javanese in which simulfix {n-} changes to {ng-} when it is attached to the bases which are begun by alveolar approximant consonant. An example of this would be the base lali in the Using dialect becomes ngelali, but in Javanese becomes nglali.